Implementasi Proses Rehabilitasi Terhadap Penyalahguna Narkotika di Panti Rehabilitasi Yayasan Anargya Bali - A.P. Komang Ayu Hariwangi; Simon Nahak; I Ketut Sukadana (Fakultas Hukum Universitas Warmadewa, 2019)
Transnational narcotics crimes are carried out using modern modus operandi and advanced technology, including safeguarding the results of narcotics crimes. The development of the quality of narcotics crimes has become a very serious threat to human life. Drug users or users on the one hand are criminals, but on the other hand are victims. According to the law, the user or drug user as the perpetrator of narcotics crime is by the provisions of the Narcotics Law which regulates imprisonment given to the perpetrators of narcotics abuse. The formulation of the problem raised is (1) what is the process of rehabilitation of narcotics abusers in the Anargya Foundation? (2) What are the obstacles in the process of rehabilitation of narcotics abusers at the Anargya Foundation? The problems that will be discussed will be examined based on an empirical perspective, empirical research, namely research carried out through observation or research directly into the field. The problem approach used in this study is an empirical juridical approach. The results showed that the process of rehabilitation of narcotics abusers at the Anargya Bali Foundation was carried out in several phases, namely the first stage (intake) aimed at making an assessment and knowing the suitability or feasibility of the treatment program with the client's condition. The second stage (primar care) is carried out by the assessment process and is considered to be eligible to undergo treatment on physical, mental and spiritual aspects. The third stage (transitional), in this phase the client is more focused on preparing himself to return to society. Whereas the fourth stage (after care) is that in this phase the client is allowed to stay outside the care facility but still conducts outpatient sessions on a regular basis to monitor the client's progress. Obstacles in the process of rehabilitation of narcotics abusers at the Anargya Bali Foundation consist of internal factors and external factors.